Investigation of silica nanoparticle-polymer hybrid stability under high temperature and salinity for oil displacement application - Ra’eis, Amer Iskandar (2023)
Polymer flooding is one of the most often utilised enhanced oil recovery (EOR) techniques because it provides excellent recovery. Polymer flooding enhances sweep efficiency and reduce viscous fingering severity by increasing fluid and oil mobility. Due to excellent viscosifying nature, and well-known physiochemical properties, partially hydrolyzed polyacrylamide (HPAM) is the polymer most often utilised for the application. However, high temperatures restrict its application because polymer will acts as shear-thinning, such it undergoes shear degradation and reduces viscosity at high shear rates and quickly destabilized and therefore unable to achieve the expected effects. High salinity also causes the molecular chain of the polymer to collapse, which results in a much smaller molecule and hence, produces a lower viscosity solution. Adding nanoparticle to polymer solutions is now required to alter their properties. Therefore, this study aims to investigate the effect of silicon dioxide nanoparticles (SiO2) addition to the stability of HPAM at high temperatures and salinity. The shear viscosity and the flooding performance at high temperature and high salinity gauge the stability of HPAM and the hybrid HPAM- SiO2. A series of stability measurements as well as core flooding experiment with variations of conditions were conducted in order to know the improvement offered by this nanoparticle towards HPAM polymer. At a temperature of 110 0C, the addition of 1 wt% SiO2 nanoparticle have enhanced the viscosity of 0.015 wt% HPAM, from 3.4 cP to 6.8 cP. This resulted in an almost 90% oil recovery rate. It also strengthened HPAM's salt tolerance at concentration of 5 wt% of NaCl by raising its viscosity up to 4.6 cP. This HPAM hybrid also have improve the oil recovery factor for this condition as well up to 85%. In conclusion, adding nanoparticles to HPAM will unquestionably increase the stability and potentially be used in EOR operations.